2009
DOI: 10.2353/ajpath.2009.080241
|View full text |Cite
|
Sign up to set email alerts
|

CCN3 (NOV) Is a Negative Regulator of CCN2 (CTGF) and a Novel Endogenous Inhibitor of the Fibrotic Pathway in an in Vitro Model of Renal Disease

Abstract: Fibrosis is a major cause of end-stage renal disease, and although initiation factors have been elucidated, uncertainty concerning the downstream pathways has hampered the development of anti-fibrotic therapies. CCN2 (CTGF) functions downstream of transforming growth factor (TGF)-beta, driving increased extracellular matrix (ECM) accumulation and fibrosis. We examined the possibility that CCN3 (NOV), another CCN family member with reported biological activities that differ from CCN2, might act as an endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
117
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 33 publications
17
117
0
Order By: Relevance
“…It is interesting to note that, as discussed above for CCN5, a similar CCN2-antagonizing function has been described for CCN3 in murine cartilage (Kawaki et al 2008) and in kidney mesangial cells (Riser et al 2009). Additional experiments will be needed to determine if CCN3 and CCN5 inhibit CCN2 function similarly but at different locations, or if their inhibitory activity is mechanistically different due to their intrinsic structural differences (CCN5 is the only CCN family member that lacks the entire C-terminal module).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that, as discussed above for CCN5, a similar CCN2-antagonizing function has been described for CCN3 in murine cartilage (Kawaki et al 2008) and in kidney mesangial cells (Riser et al 2009). Additional experiments will be needed to determine if CCN3 and CCN5 inhibit CCN2 function similarly but at different locations, or if their inhibitory activity is mechanistically different due to their intrinsic structural differences (CCN5 is the only CCN family member that lacks the entire C-terminal module).…”
Section: Discussionmentioning
confidence: 99%
“…In example, rhTGF-β1, acting through the TGF-β type 1 receptor, has recently been shown to induce CCN1 and CCN2, and in a reciprocal fashion to inhibit CCN3 gene expression in skin fibroblasts (Thompson et al 2014). In some cases differing CCN family members have been shown to have balancing, and antagonistic cell and tissue effects; for example, CCN3 may suppress CCN1 and CCN2-dependent activities (Riser et al 2009;Perbal 2013). We have previously shown that rhTGF-β1 induces CCN2 in adipocyte differentiation (Tan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as some members of the CCN family, notably CCN3 and CCN5 block the fibrogenic action of CCN2, it is possible that CCN3 and CCN5 may be used in the future to treat fibrotic diseases such as SSc (Riser et al 2009;Leask 2009;Yoon et al 2010). …”
Section: Connective Tissue Growth Factor (Ctgf Ccn2)mentioning
confidence: 99%